Faktor Meningkatnya Partisipasi Politik Masyarakat pada Pilkada Masa Covid-19 di Kabupaten Dharmasraya Perspektif Siyasah Syar’iyyah - Cipta Samiri Putri Zari Putri; Achmadin Damanik Damanik (Yayasan Lembaga Studi Makwa, 2022)
This research is motivated by two things. First, the increase in community political participation in Dharmasraya Regency in the 2020 Pilkada compared to the previous year's Pilkada. Second, it is carried out in a Covid-19 emergency situation. This study aims to find out why the level of political participation of the people of Dharmasraya Regency in the 2020 Pilkada increased in the Covid-19 emergency situation and how according to the perspective of siyasah syar'iyyah on community political participation in Dharmasraya Regency. The type of research that the author uses in this research is field research conducted in Dharmasraya Regency, West Sumatra Province. Sources of primary data obtained through observations, interviews and documentation conducted on the relevant stakeholders. Based on the results of the study, it can be found that the factors that influence the political participation of the community in Dharmasraya Regency in the 2020 Pilkada are due to the driving factors, namely the awareness or political stimulant factor of the community, political situation or environmental factors, political education factors and trust factors in the government. According to the siyasah syar'iyyah perspective on community political participation in the Pilkada of Dharmasraya Regency, it is already practicing the commands of Allah SWT or in accordance with Islamic teachings that require humans to participate in the election of leaders for the benefit of the people which is mandatory.